2019
DOI: 10.3390/en12112074
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Fluid Dynamic Behaviors of Confined Slot Jets Impinging on an Isothermal Moving Surface with Nanofluids

Abstract: A two-dimensional numerical investigation of turbulent convective heat transfer due to a confined slot jet impinging on an isothermal moving surface is accomplished. The confined geometry has an upper adiabatic surface parallel to the heated moving plate and the slot jet is in the middle of the confining adiabatic wall. The working fluids are pure water or a nanofluid, which in this case was a mixture of water and Al2O3 nanoparticles. The governing equations are written adopting the k-ε turbulence model with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…The forced and natural convective heat transfer behaviours of nanofluids in various mediums have been studied. Such studies as the heat transfer behaviour of nanofluids in cavities [309][310][311][312][313], porous materials [314][315][316] and jet impinging [317] all show an increase in the dimensionless heat transfer parameter with the addition of nanoparticles. These studies prove the tremendous potentials of nanofluids in the electronics and data storage industries.…”
Section: Nanofluids In Electronic Coolingmentioning
confidence: 99%
“…The forced and natural convective heat transfer behaviours of nanofluids in various mediums have been studied. Such studies as the heat transfer behaviour of nanofluids in cavities [309][310][311][312][313], porous materials [314][315][316] and jet impinging [317] all show an increase in the dimensionless heat transfer parameter with the addition of nanoparticles. These studies prove the tremendous potentials of nanofluids in the electronics and data storage industries.…”
Section: Nanofluids In Electronic Coolingmentioning
confidence: 99%
“…The average Nusselt number increased as Reynolds numbers increased similar to that of a restricted slot jet impingement on a flat target surface, with the highest significant values observed for a distance of 10 mm between the jet and the target 20 . The rate of heat transfer on an isothermally heated flat target plate of a restricted slot jet impingement is quantitatively examined by Buonomo et al 21 The average skin friction coefficient increases as the dimensionless surface velocity drops with increasing Reynolds number for all jet‐to‐target spacing. In another study, it has been shown that the heat transfer coefficient increased as the Reynolds number increased and as the distance between the jet and the target decreased 22 .…”
Section: Introductionmentioning
confidence: 99%
“…They carried out a numerical study by employing the phase shift between walls and reported optimal performance in the low-Re region with a phase shift of zero. Manca et al [31] performed computational analysis of the thermal and flow performance of NF inside a ribbed duct and reported an enhancement in the Nu and pressure drop (PD) with an increase in the VF of NPs and Re. Mohammed et al [32] also reported similar results for their numerical investigation.…”
Section: Introductionmentioning
confidence: 99%